Perfect numbers!

Given this natural number

2 500000000000978 × 4 929850984395 × 29 908756489738 { 2 }^{ 500000000000978 }\quad \times \quad { 4 }^{ 929850984395 }\quad \times \quad { 29 }^{ 908756489738 }

Is it a perfect number(a positive integer which is equal to sum of its proper divisors)?

Bonus: Prove it!

True Not enough information False

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chris Galanis
Aug 1, 2015

Let A A be the natural number such that A = 2 500000000000978 4 929850984395 2 9 908756489738 A = 2^{500000000000978}\cdot 4^{929850984395}\cdot 29^{908756489738}

Then we get that A = 2 500000000000978 ( 2 2 ) 929850984395 2 9 908756489738 A = 2^{500000000000978}\cdot (2^2)^{929850984395}\cdot 29^{908756489738}

A = 2 500000000000978 + 2 929850984395 2 9 908756489738 \Rightarrow A = 2^{500000000000978+2\cdot929850984395}\cdot 29^{908756489738}

A = 2 x 2 9 y \Rightarrow \boxed {A = 2^{x} \cdot 29^{y}} (no need to write the exponents...)

So since 2 2 and 29 29 are both prime numbers, every single divisor of A A is of the form: 2 n 2 9 k 2^{n}\cdot 29^{k} for n 0 , 1 , 2 , . . . ( x 1 ) , x n \in 0, 1, 2, ... (x-1), x and k 0 , 1 , 2 , . . . ( y 1 ) , y k \in 0, 1, 2, ... (y-1), y

Thus by using some simple combinatorics we get that A A has ( x + 1 ) ( y + 1 ) (x+1)\cdot (y+1) divisors including itself.

Hence all the divisors are: ( 2 0 2 9 0 ) , ( 2 0 2 9 1 ) , ( 2 0 2 9 2 ) , . . . ( 2 x 2 9 y 2 ) , ( 2 x 2 9 y 1 ) , ( 2 x 2 9 y ) (2^0\cdot 29^0), (2^0\cdot 29^1), (2^0\cdot 29^2),...(2^x\cdot 29^{y-2}), (2^x\cdot 29^{y-1}), (2^x\cdot 29^y)

Now, by the definition of the perfect number ("A number is perfect when the sum of its divisors (except the number itself) equals the given number.") we assume that the following equation is true:

2 A = ( 2 0 2 9 0 ) + ( 2 0 2 9 1 ) + ( 2 0 2 9 2 ) + . . . + ( 2 x 2 9 y 2 ) + ( 2 x 2 9 y 1 ) + ( 2 x 2 9 y ) 2\cdot A = (2^0\cdot 29^0)+(2^0\cdot 29^1)+(2^0\cdot 29^2)+...+(2^x\cdot 29^{y-2})+(2^x\cdot 29^{y-1})+(2^x\cdot 29^y)

2 A = 2 0 ( 2 9 0 + 2 9 1 + . . . + 2 9 y 1 + 2 9 y ) + 2 1 ( 2 9 0 + 2 9 1 + . . . + 2 9 y 1 + 2 9 y ) + . . . + 2 x ( 2 9 0 + 2 9 1 + . . . + 2 9 y 1 + 2 9 y ) \Rightarrow 2\cdot A = 2^0\cdot(29^0+29^1+...+29^{y-1}+29^y)+2^1\cdot(29^0+29^1+...+29^{y-1}+29^y)+...+2^x\cdot(29^0+29^1+...+29^{y-1}+29^y)

2 A = ( 2 9 0 + 2 9 1 + . . . + 2 9 y 1 + 2 9 y ) ( 2 0 + 2 1 + . . . + 2 x 1 + 2 x ) \Rightarrow 2\cdot A = (29^0+29^1+...+29^{y-1}+29^y)\cdot (2^0+2^1+...+2^{x-1}+2^x)

So by the sum formula of geometric progression we get:

2 A = 1 ( 1 2 9 y + 1 ) 1 29 1 ( 1 2 x + 1 ) 1 2 2\cdot A = \frac{1\cdot (1 - 29^{y+1})}{1 - 29}\cdot\frac{1\cdot (1 - 2^{x+1})}{1 - 2}

2 A = ( 2 9 y + 1 1 ) 28 ( 2 x + 1 1 ) \Rightarrow 2\cdot A = \frac{(29^{y+1} - 1)}{28}\cdot (2^{x+1} - 1)

8 A = ( 2 9 y + 1 1 ) 7 ( 2 x + 1 1 ) \Rightarrow 8\cdot A = \frac{(29^{y+1} - 1)}{7}\cdot (2^{x+1} - 1)

And it's true that [ 2 9 y + 1 1 ] 0 ( m o d 7 ) [ ( 28 + 1 ) y + 1 1 ] 0 ( m o d 7 ) [29^{y+1}-1]\equiv 0 (mod 7) \Rightarrow [(28+1)^{y+1}-1] \equiv 0 (mod 7) and we can prove this through the binomial theorem such that: ( 28 + 1 ) y + 1 = ( y + 1 0 ) 2 8 y + 1 1 0 + ( y + 1 1 ) 2 8 y 1 1 + . . . + ( y + 1 y ) 2 8 1 1 y + ( y + 1 y + 1 ) 2 8 0 1 y + 1 (28+1)^{y+1} = \binom{y+1}{0}28^{y+1}\cdot1^0 + \binom{y+1}{1}28^{y}\cdot1^1 + ... + \binom{y+1}{y}28^1\cdot1^y + \binom{y+1}{y+1}28^0\cdot1^{y+1}

( 28 + 1 ) y + 1 = ( y + 1 0 ) 2 8 y + 1 1 0 + ( y + 1 1 ) 2 8 y 1 1 + . . . + ( y + 1 y ) 2 8 1 1 y + 1 \Rightarrow (28+1)^{y+1} = \binom{y+1}{0}28^{y+1}\cdot1^0 + \binom{y+1}{1}28^{y}\cdot1^1 + ... + \binom{y+1}{y}28^1\cdot1^y + 1

And by substituting we get: [ ( y + 1 0 ) 2 8 y + 1 1 0 + ( y + 1 1 ) 2 8 y 1 1 + . . . + ( y + 1 y ) 2 8 1 1 y + 1 1 ] 0 ( m o d 7 ) [\binom{y+1}{0}28^{y+1}\cdot1^0 + \binom{y+1}{1}28^{y}\cdot1^1 + ... + \binom{y+1}{y}28^1\cdot1^y + 1 -1] \equiv 0 (mod7)

28 [ ( y + 1 0 ) 2 8 y 1 0 + ( y + 1 1 ) 2 8 y 1 1 1 + . . . + ( y + 1 y ) 2 8 0 1 y ] 0 ( m o d 7 ) 28\cdot [\binom{y+1}{0}28^{y}\cdot1^0 + \binom{y+1}{1}28^{y-1}\cdot1^1 + ... + \binom{y+1}{y}28^0\cdot1^y ]\equiv 0 (mod7) which is true since 7 28 7|28 and ( 2 9 y + 1 1 ) 7 = 4 z \frac{(29^{y+1}-1)}{7} = 4\cdot z for z = ( y + 1 0 ) 2 8 y 1 0 + ( y + 1 1 ) 2 8 y 1 1 1 + . . . + ( y + 1 y ) 2 8 0 1 y z = \binom{y+1}{0}28^{y}\cdot1^0 + \binom{y+1}{1}28^{y-1}\cdot1^1 + ... + \binom{y+1}{y}28^0\cdot1^y

Thus in the main equation we get:

8 A = 4 z ( 2 x + 1 1 ) 8\cdot A = 4\cdot z \cdot (2^{x+1} - 1)

2 A = z ( 2 x + 1 1 ) \Rightarrow 2\cdot A = z\cdot (2^{x+1} - 1)

However 2 A 2\cdot A is an even number while z ( 2 x + 1 1 ) z\cdot (2^{x+1} - 1) is not since both z z and ( 2 x + 1 1 ) (2^{x+1}-1) are odd numbers:

2 x + 1 0 ( m o d 2 ) ( 2 x + 1 1 ) 1 ( m o d 2 ) 2^{x+1}\equiv 0 (mod2)\Rightarrow (2^{x+1}-1)\equiv 1 (mod 2) and...

z = ( y + 1 0 ) 2 8 y 1 0 + ( y + 1 1 ) 2 8 y 1 1 1 + . . . + ( y + 1 y 1 ) 2 8 1 1 y 1 + ( y + 1 y ) 2 8 0 1 y z = \binom{y+1}{0}28^{y}\cdot1^0 + \binom{y+1}{1}28^{y-1}\cdot1^1 + ... + \binom{y+1}{y-1}28^1\cdot 1^{y-1} + \binom{y+1}{y}28^0\cdot1^y

z = 28 ( ( y + 1 0 ) 2 8 y 1 1 0 + ( y + 1 1 ) 2 8 y 2 1 1 + . . . + ( y + 1 y 1 ) 2 8 0 1 y 1 ) + ( y + 1 y ) 2 8 0 1 y z = 28\cdot (\binom{y+1}{0}28^{y-1}\cdot1^0 + \binom{y+1}{1}28^{y-2}\cdot1^1 + ... + \binom{y+1}{y-1}28^0\cdot 1^{y-1}) + \binom{y+1}{y}28^0\cdot1^y

z = 28 ( ( y + 1 0 ) 2 8 y 1 1 0 + ( y + 1 1 ) 2 8 y 2 1 1 + . . . + ( y + 1 y 1 ) 2 8 0 1 y 1 ) + ( y + 1 ) z = 28\cdot (\binom{y+1}{0}28^{y-1}\cdot1^0 + \binom{y+1}{1}28^{y-2}\cdot1^1 + ... + \binom{y+1}{y-1}28^0\cdot 1^{y-1}) + (y+1) and because y y is even ( 2 5 + 8 8 ( m o d 10 ) (2\cdot 5 + 8\equiv 8(mod 10) <--last digits of the exponents ) ) then z z is odd.

Hence, since the above equation is not true then A A is not as perfect as it seems!

Huân Lê Quang
Aug 3, 2015

Observe the number:

2 500000000000978 4 929850984395 2 9 908756489738 2^{500000000000978}\cdot 4^{929850984395}\cdot 29^{908756489738}

Obviously, it's an even number. Now, analyze the sum of its proper divisors. Because 29 is an odd prime number, so the given number has:

908756489738 + 1 908756489738 + 1 = 908756489739 908756489739 odd proper divisors

As we know, sum of an odd number of odd numbers is an odd number. Furthermore, sum of an odd number and an even number is an odd number. Therefore, sum of the given number's proper divisors is an odd number. But the given number is an even number, so it isn't a perfect number.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...